2012
DOI: 10.1002/14651858.cd007672.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve continuity of care in the follow-up of patients with cancer

Abstract: Results from this Cochrane review do not allow us to conclude on the effectiveness of included interventions to improve continuity of care on patient, healthcare provider or process of care outcomes. Future research should evaluate interventions that target an improvement in continuity as their primary objective and describe these interventions with the categories proposed in this review. Also of importance, continuity measures should be validated with persons with cancer who have been followed in various sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 152 publications
1
91
0
2
Order By: Relevance
“…However, effective interventions to improve continuity of care, particularly for patients with cancer, have proved elusive 18. The results presented here suggest that ensuring continuity of care by community staff is seen as highly important by the family carers of patients dying at home, but such care continuity was often absent.…”
Section: Discussionmentioning
confidence: 80%
“…However, effective interventions to improve continuity of care, particularly for patients with cancer, have proved elusive 18. The results presented here suggest that ensuring continuity of care by community staff is seen as highly important by the family carers of patients dying at home, but such care continuity was often absent.…”
Section: Discussionmentioning
confidence: 80%
“…Three of the reviews focus on continuity of care and unscheduled secondary care 9 10 13. The reviews by Cabana and Hsiao looked at continuity of primary healthcare and unscheduled secondary care, but the data are over 5 years old.…”
Section: Discussionmentioning
confidence: 99%
“…However, both these reviews reflect the updated findings of our review, namely that continuity of care reduces unscheduled secondary care. The review by Aubin et al 9 only focuses on patients with cancer and considered studies across primary and secondary care.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion was drawn in the review of Aubin et al on the effects of interventions to improve continuity of follow-up care for cancer patients. In this review, a shared care model was used in 14 of 63 studies, and even though some effects in separate studies were found, no clear conclusions could be drawn because the results were too mixed [35]. Again, just as in the review of Smith et al [7,18], the interventions were complex, which makes it hard to determine which elements of the intervention were effective and which were not.…”
Section: Discussionmentioning
confidence: 99%